The Influence of Balanced Nutrition Extension Through Poster Media on the Improvement of Knowledge and Change Attitude - Oslida Martony (International Journal of Science and Society, 2019)
The purpose of this study was to determine the Effect of Balanced Nutrition Counseling through Poster Media on Knowledge Enhancement and Attitude Change of School Children in MIN Medan Senembah Kec. Tanjung Morawa. This research is an experimental study using design before and after the intervention using an external comparison group. The population was 346 students in grades 3,4 and 5—the research sample of 78 student samples. Data collected are before and after knowledge, before and after attitude. The method uses a questionnaire. Data collection is done by questionnaire form. Data analysis uses Paired Sample T-Test and Independent T-Test tests. The results obtained by the common knowledge before counseling in the experimental group are 62.87, and in the comparison group is 49.45. The average post-counseling knowledge in the experimental group was 76.17, and in the comparison group was 61.12. The average attitude before in the experimental group was 68.31 and in the comparison group 62.97. The average attitude after the experimental group was 73.85, and the comparison group was 68.95. There were significant differences in knowledge and attitudes before and after counseling (p-value = 0.000> 0.05). There were no differences in knowledge and attitudes between the experimental and comparison groups (p-value = 0.490> 0.05).